KONSEP DASAR AKIDAH AKHLAK DI SEKOLAH ATAU MADRASAH - Nuryanto Putra, Johanna; Anharudin; Yandi, Muhammad; Ruwanda, Alwi; Muliana, Zahqy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study of Islamic Beliefs and Ethics plays a strategic role in helping students develop faith, piety, and good moral character through a dynamic process of interaction between teachers, students, and their learning environment. The curriculum, which covers aspects of faith as well as praiseworthy and blameworthy moral conduct, is designed to foster an understanding of and practice of Islamic values in their daily lives. However, its implementation is often hindered by a lack of variety in teaching approaches, teachers’ weak mastery of the subject matter, a curriculum that is out of context, unengaging teaching methods, and low student motivation. Therefore, an update to learning strategies and a reinforcement of Pancasila values are necessary to ensure that Akidah Akhlak education can shape a generation that is faithful, of noble character, responsible, and plays a positive role in social and national life